Correction: Cardiovascular Health in India - a Report Card from Three Urban and Rural Surveys of 22,144 Adults - Roopa Shivashankar; Kalpana Singh; Dimple Kondal; Ruby Gupta; Pablo Perel; Deksha Kapoor; Devraj Jindal; Sailesh Mohan; Rajendra Pradeepa; Prashant Jarhyan; Nikhil Srinivasapura Venkateshmurthy; Nikhil Tandon; et al. (Ubiquity Press, 2022)
This article details a correction to: Shivashankar R, Singh K, Kondal D, Gupta R, Perel P, Kapoor D, et al.. Cardiovascular Health in India - a Report Card from Three Urban and Rural Surveys of 22,144 Adults. Global Heart. 2022; 17(1): 52. DOI: http://doi.org/10.5334/gh.1137